Quantitative Analysis of hsa-miR-21-5p Expression in Human Umbilical Cord Mesenchymal Stem Cell-derived Exosomes Under Hypoxia - Muhammad, Daisy Ramadhani; Barlian, Anggraini; Murti, Harry; Prawira, Matheus Alvin; Faza, Naufalia (Bogor Agricultural University, Indonesia, 2025)
Exosomes have emerged as a cell-free alternative to mesenchymal stem cells (MSCs). Hypoxic preconditioning might result in the production of exosomes with ideal properties. As such, the effect of hypoxia on hsa-mir-21-5p expression, which is known to contribute to the immunomodulatory activity of exosomes, should be investigated. This research aimed to enrich and characterize exosomes from human umbilical cord MSC (hUC-MSC) secretome samples secreted under hypoxia and normoxia, as well as to analyze the expression of hsa-miR-21-5p in each sample. Secretomes were collected from cultured cells under both hypoxic and normoxic conditions, and exosomes were subsequently enriched from the secretomes through ultrafiltration. In this research, it was found that particles in N-Exo and H-Exo exhibited round morphology, expressed exosomal CD81 and CD63 markers with an average size of 153.7 ± 31.3 nm and 137.7 ± 25.0 nm, respectively. N-Exo and H-Exo can also be internalized by mesenchymal stem cells (MSCs). qRT-PCR results then indicated that hsa-miR-21-5p expression was significantly lower in H-Exo (p < 0.05). In conclusion, hypoxic preconditioning, as performed in this research, was also found to affect hsa-miR-21-5p and downregulate its expression in hypoxic samples relative to controls.